The Determinants of Loan Loss Provisions in Islamic Banking - Al-Khayat, Laith (2013)
Only recently have regulators and academics started to pay special attention to alternative methods of banking. Islamic banks offer a unique environment considering they are fundamentally different due to the fact they follow Shariah law. The purpose of this research is to examine the key determinants behind loan loss provisions in the Islamic banking industry. The study then compares the results to the determinants of conventional banks and explores the reasons behind these underlying differences in provisioning behaviour. This study uses a sample of 57 Islamic banks, operating in 15 countries over the period of 2002-2012. It utilises two main models: an Ordinary Least Squares regression model and a dynamic Generalised Method of Moments Arellano-Bond estimator. The main determinants are found to be tier 1 capital, non-performing loans and size. The results confirm that Islamic banks are prudent and not procyclical. They also confirm that the banks do not income-smooth except when they suffer negative earnings, acting as a countercyclical tool. These findings reveal that Islamic banks’ provisioning behaviour is very different to conventional banks across the world allowing them to avoid magnifying the impact of the economic cycle on their income and capital.